Occurrence of Thelazia rhodesii Infection in a Jersey Crossbred Cow – A Case Report - Rangasamy, Velusamy; Annamalai, Latchumikanthan; Kanniappan, Vijayasarathi Matheri; Arunachalam, Kumaresan (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Thelaziosis is a helminthic disease caused by spirurid nematode of the genus Thelazia, which causes infection in orbital tissues of several animals including cattle, horses, dogs and humans worldwide (Otranto et al., 2001). Cattle are mainly infected by Thelazia rhodesii, Thelazia gulosa, and Thelazia skrjabini. Among these, Thelazia rhodesii is the most common parasite affecting cattle in many countries (Otranto et al., 2001). Horses, camels, and dogs are primarily infected by T. lacrimalis, T. leesei and T. callipaeda, respectively. It is mainly transmitted by secretophagous flies that feed on lacrimal secretions such as non-biting dipteran flies of the genus Musca (Muscidae) (Giangaspero et al., 2000). Face flies, viz., Musca autumnalis, Musca convexifrons and Musca larvipara have been incriminated as vectors for Thelazia species infesting cattle and horses (Giangaspero et al., 2000). The rate of infection is high during summer and rainy seasons when the fly population is abundant (Venkatesan et al., 2019). Clinically, thelaziosis is considered as an important parasitic disease because of its zoonotic nature (Otranto et al., 2007). In the definitive hosts, the larval stages and adults cause excessive lacrimation, epiphora, conjunctivitis, keratitis and corneal ulcers (Deepthi and Yalavarthi, 2012). Bovine thelaziosis was first reported in Iran by Ebadi in 1951 and other investigators in many countries, however only limited studies are recorded in India (Arunachalam et al., 2017; Sivajothi et al., 2023). This case report focused on the occurrence, identification, clinical and therapeutic management of Thelazia rhodesii infection in a Jersey crossbred cow in central part of Tamil Nadu.